Policy Formulation Based on Local Traditions - Rivaldi, Rivaldi; Kartini, Dede Sri; Yuningsih, Neneng Yani (Journal La Sociale, 2025)
This study aims to analyze the process of formulating public policies based on local traditions implemented through Paruman in Bayung Gede Traditional Village, Kintamani District, Bangli Regency, Bali Province. Paruman was chosen as the object of research because it is a traditional deliberation forum that still exists and is used in making decisions on village development. The research method used is qualitative with data collection techniques through literature studies and field studies in the form of observation, interviews, and documentation. Data analysis was carried out descriptively by referring to the stages of public policy formulation. The results of the study indicate that the existence of Paruman is influenced by internal factors of the indigenous community and external factors from the government. The implementation of Paruman has similarities with village deliberations in general, but differs in terms of the basis for decision-making that refers to local customary values and traditions. Paruman in Bayung Gede Village has fulfilled the stages of policy formulation, starting from identifying problems, setting agendas, selecting alternatives, to making decisions. The conclusion of this study shows that the formulation of public policies based on local traditions through Paruman in Bayung Gede Traditional Village uses a participatory and contextual deliberative model with the cultural values of the local community.